2013
DOI: 10.33073/pjm-2013-032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allicin on the Formation of Pseudomonas aeruginosa Biofilm and the Production of Quorum-Sensing Controlled Virulence Factors

Abstract: The Gram-negative Pseudomonas aeruginosa bacterial pathogen is reputed for its resistance to multiple antibiotics, and this property is strongly associated with the development of biofilms. Bacterial biofilms form by aggregation of microorganisms on a solid surface and secretion of an extracellular polysaccharide substances that acts as a physical protection barrier for the encased bacteria. In addition, the P aeruginosa quorum-sensing system contributes to antibiotic resistance by regulating the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 34 publications
4
24
0
1
Order By: Relevance
“…Dimethyl thiosulfinate inhibited P. aeruginosa, whereas allicin appeared to be inactive against the pathogen. Meanwhile, it was demonstrated that allicin inhibits biofilm formation by P. aeruginosa ATCC 27853 PAO1 but did not show the inhibitory effect on bacterial growth .…”
Section: Resultsmentioning
confidence: 99%
“…Dimethyl thiosulfinate inhibited P. aeruginosa, whereas allicin appeared to be inactive against the pathogen. Meanwhile, it was demonstrated that allicin inhibits biofilm formation by P. aeruginosa ATCC 27853 PAO1 but did not show the inhibitory effect on bacterial growth .…”
Section: Resultsmentioning
confidence: 99%
“…Organosulfur compounds from garlic were shown to inhibit QS in opportunistic human pathogens (Ta & Arnason, 2015). Lipophilic allicin could inhibit early bacterial adhesion, reduce the secretion of extracellular polymeric substances, and downregulate the production of virulence factors, indicating its potential as a therapeutic agent for controlling P. aeruginosa biofilm formation (Lihua, Jianhuit, Jialini, Yayin, & Guanxin, 2013). In vitro data have also shown a decrease in virulence factors and reduced production of quorum-sensing signals by P. aeruginosa in the presence of fresh garlic extract (Harjai, Kumar, & Singh, 2010).…”
Section: Fermented Black Garlicmentioning
confidence: 99%
“…2-aminoacetophenone virulence factor [223] alkylquinoline signaling molecule [224] CFTR inhibitory factor virulence factor [225,226] elastase [227] ETA [228] ExoS virulence factor [228][229][230][231] ExoT virulence factor [228,229] Exotoxin A virulence factor [227,232] ExoU virulence factor [233][234][235][236][237] L-2-amino-4-methoxy-3-butenoic acid [238] lipopolysaccharide (LPS) endotoxin [239,240] Database on potential toxigenic capacities of microorganisms used for industrial production…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%